B Corps: A Socioeconomic Approach for the Covid-19 Post-Crisis - Castillo-Guajardo, D (Frontiers Media S.A., 2020)
The current global health and economic crisis caused by COVID-19 has opened the possibility to adopt the B Corp model and focus more on the person. Based on grounded theory, we have examined 147 organizations from 14 countries listed at the B Corp Directory for Latin America. Latin American B Corps have traits linked to family-related issues that are distinct from other B Corps located in different continents. Our main findings are that B Corps develop a more inclusive and sustainable economy to benefit society, go beyond the notion of CSR, and move away from traditional companies, as B Corps combine social development and economic growth. © Copyright © 2020 Saiz-Álvarez, Vega-Muñoz, Acevedo-Duque and Castillo.